2017
DOI: 10.1111/nph.14482
|View full text |Cite
|
Sign up to set email alerts
|

TSV, a putative plastidic oxidoreductase, protects rice chloroplasts from cold stress during development by interacting with plastidic thioredoxin Z

Abstract: Rice is vulnerable to cold stress. Seedlings are very sensitive to cold stress and this harms global rice production. The effects of cold on chloroplast development are well known, but little is known about the underlying molecular mechanisms. Here, we isolated a temperature-sensitive virescent (tsv) mutant that is extremely sensitive to cold stress. It displayed defective chloroplasts, decreased chlorophyll and zero survivorship under cold stress. We isolated and identified TSV by map-based cloning and rescue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 39 publications
0
55
0
Order By: Relevance
“…In rice, OsTRXz interacts with OsCHLI (subunit I of magnesium chelatase), which catalyzes the first committed step of chlorophyll biosynthesis (Zhang et al ). TCD5/TSV protects rice chloroplasts from cold stress by interacting with OsTRXz (Wang et al ; Sun et al ). In the current study, we found that OsTRXz interacts with OsFLN1 and HSA1/OsFLN2, regulating the transcription of PEP‐related genes and chloroplast biogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In rice, OsTRXz interacts with OsCHLI (subunit I of magnesium chelatase), which catalyzes the first committed step of chlorophyll biosynthesis (Zhang et al ). TCD5/TSV protects rice chloroplasts from cold stress by interacting with OsTRXz (Wang et al ; Sun et al ). In the current study, we found that OsTRXz interacts with OsFLN1 and HSA1/OsFLN2, regulating the transcription of PEP‐related genes and chloroplast biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…OsFLN1 and HSA1/OsFLN2 interact with OsTRXz in vitro and in vivo Thirty-five components were identified in the Arabidopsis and mustard TAC complex, and FLNs incorporated into the TACs complex by interacting with other components to regulate PEP-related gene expression in Arabidopsis (Reiss and Link 1985;Pfalz et al 2006;Arsova et al 2010;Gilkerson et al 2012;Huang et al 2013). Homologs of TCD5/TSV in Arabidopsis plastids have not been identified as components of TACs, but TCD5/TSV interacts with OsTRXz and enhances OsTRXz stability at low temperatures in rice (Wang et al 2016c;Sun et al 2017). This suggests that chloroplast biogenesis and development differ somewhat between dicotyledonous and monocotyledonous plants.…”
Section: Expression and Subcellular Location Of Osfln1mentioning
confidence: 99%
See 1 more Smart Citation
“…Low‐temperature stress causes obvious damage to plants, including wilting, discoloration, drying of leaf edges, accelerated aging, incomplete ripening, and even death. Moreover, chlorotic leaves or albino phenotypes occur under cold‐stress conditions and the key genes, such as OsV4 ( Oryza sativa Virescent 4 ), TCD10 ( Thermo‐sensitive Chlorophyll‐deficient mutant 10 ), TCD11 ( Thermo‐sensitive Chlorophyll‐deficient mutant 11 ), TSV ( Thermo‐sensitive Virescent mutant ), and TSV3 ( Thermo‐sensitive Virescent mutant 3 ) are essential for chloroplast development at low temperatures in Arabidopsis (Gong et al ; Wu et al ; Sun et al ; Wang et al ; Lin et al ). Lateral roots are model tissues for studying the response to cold stress in Arabidopsis .…”
Section: Trade‐off Between Plant Development and Defense During Adaptmentioning
confidence: 99%
“…2008). OsTRXz interacts with TSV to protect chloroplast development under cold stress (Sun et al . 2017).…”
Section: Discussionmentioning
confidence: 99%